Topography and the Road Network in the Territory of Ancient Naissus - Ljubomirović, Irena V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Archaeological research revealed that ancient Naissus was located on the right bank of the Nišava, on the territory partially covered by the Niš Fortress. The ancient town developed on a wide and flat terrain, which offered good conditions for settlement, but also for raising fortifications. According to modern scholars, the urban settlement on the right bank of the Nišava was preceded by a small native village (vicus), which was important for the erection of the town fortifications. Numerous roads were linking Naissus with the surrounding regions and villas in the countyside. We learn about them on the basis of epigraphic and archaeological material milestones and remains of roads, but also on the basis of the location of the necropolises, which in the classical period often sprang up near the suburban roads. The road leading to the east crossed the Nišava by a stone bridge, whose remains were visible not far from today’s „Benetton“ factory. The road led further over „Gabrovac land“, intersected with streams over which the remains of three stone bridges from the Roman period were found. This route led to Mediana, a suburb with villas three miles distant from the city. Another important road connecting the region Pomoravlje with the southern parts of the province of Dalmatia was the road Naissus-Lissus. TA section leding to Macedonia and the harbour of Thessalonica over Scupi branched from it south of Naissus: Ad Herculem, Hammeum Ad Fines, Vindenae and Vicianum. FromVicianum station (Vučitrn) one section ran towards Lissus and another towards Scupi. Throughout the Timok valley stretched one of the most important roads (Naissus-Ratiaria) that linked Naissus and the central Balkan areas with the region of Podunavlje (the Danube basin). The road led from Naissus to the East, along the right bank of the Nišava (across the areas of Jagodin mala and Vrežina) and, at the modern village of Malča, it turned towards the North, following the route of the modern road and railroad to Svrljig. Further to the northeast, the road led through the valley of Svrljiški Timok and was passing through Plužina where a milestone of Trebonian Gallus was discovered (251–253 AD). The road left the river valley near a place called Palilula because the river was entering impassable canyons, and the road ran south of Knjaževac over the mountain pass Tresibaba, where it connected to the sections that led from the West (Praesidium Pompei) and the South (Turres, Remesiana). Epigraphic monuments are of particular importance for studying the history of ancient Nais. These provide valuable informtion on the way of life, customs, religion, government, military and social organization of this city. Funerary inscriptions often contain data that could be used in topography or onomastic research. Honorary inscription set up by the city councils supply information about the communities that erected them.